2010
DOI: 10.1111/j.1467-9507.2008.00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Self-representations in Early Adolescence: Variations in Sibling Similarity by Sex Composition and Sibling Relationship Qualities

Abstract: Self-representations play an important role in adolescent development. This study compared self-representations for siblings and explored whether sibling relationship characteristics are associated with similarities or differences in sibling self-concepts. We examined self-representations of 438 adolescent sibling dyads (M age younger sibling = 11.6 years, M age older = 14.3 years), finding that siblings are, on average, similar in their self-representations. This similarity varied, however, depending on sex c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…When defining closeness independent of a shared peer network, there is some evidence that closeness and warmth may moderate sibling similarity in outcomes we typically think of as positive, such as global self-worth (Gamble et al, 2010). For example, using a measure similar to the one used in this study, Gamble and colleagues found that the warmer the sibling relationship, the greater sibling similarity in high self-worth, supporting anaclitic identification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When defining closeness independent of a shared peer network, there is some evidence that closeness and warmth may moderate sibling similarity in outcomes we typically think of as positive, such as global self-worth (Gamble et al, 2010). For example, using a measure similar to the one used in this study, Gamble and colleagues found that the warmer the sibling relationship, the greater sibling similarity in high self-worth, supporting anaclitic identification.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is increasing support for the concept of anaclitic identification; close and warm relationships with siblings have been associated with greater sibling similarity, and lower warmth has been associated with less similarity in adjustment outcomes (Gamble et al, 2010; McHale et al, 2009; Rende, Slomkowski, Lloyd-Richardson, & Niaura, 2005; Rowe & Gulley, 1992). For example, Slomkowski et al (2005) found that when siblings were high in social connection (i.e., when they spent a lot of time together, had strong affection for each other, and had mutual friends), they were more likely to be similar in their tobacco use.…”
Section: Theoretical Explanationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has found significant similarities in self-esteem rank order and self-esteem mean levels between siblings (Gamble et al 2011), with some studies showing that sibling relationship quality influences the degree of similarity between siblings' self-esteem. For example, Gamble et al (2010) found that greater warmth between siblings is linked to greater similarity in their self-perceptions, while conflict is related to greater dissimilarity (Gamble et al 2010). Others have found that warm and supportive sibling relationships in childhood and adolescence are related to higher self-esteem, demonstrating that siblings provide support and companionship across the life span (Sherman et al 2006).…”
Section: Self-esteem and Sibling Relationshipsmentioning
confidence: 99%
“…In families in which one sibling reports thoughts of suicide and the other sibling does not, such an occurrence may reflect evidence of sibling de-identification. Several studies document sibling de-identification on a number of psychological characteristics (e.g., Feinberg & Hetherington, 2000) such as self-concept (Gamble, Yu, & Card, 2009) and gender role orientation (McHale, Updegraff, Helms-Erikson, & Crouter, 2001). The possible connection between de-identification and suicide ideation has never been explored.…”
mentioning
confidence: 99%